Phenology, mass accumulation patterns and growing degree days in common bean: Fenología, patrones de acumulación de masa y grados día de crecimiento en fríjol común - Pinzón-Sandoval, Elberth Hernando; Carvalho Silva, Wellington; Marchiori, Paulo Eduardo Ribeiro (Revista de Ciencias Agrícolas, 2024)
The common bean represents approximately half of the global production of leguminous grains. Brazil is the world's largest producer, as it is a primary source of protein in the population's diet. This research aimed to relate the phenological stages of the common bean under greenhouse conditions and establish a connection between mass accumulation patterns and the environment, specifically temperature, by estimating Growing Degree Days (GDD) during two periods with different temperatures throughout the year. Once a week, after seed germination, plants were collected and weighed to quantify fresh and dry mass to determine biomass allocation within the plant. This procedure was carried out until the plant’s growth cycle was completed. The environment was systematically monitored using a thermo-hygrometer. GDD accumulation was estimated for the phenological stages from V0 to R8 during two evaluation periods. Fresh and dry mass accumulation was fitted to logistic models that generated sigmoidal-type curves. It was observed that the bean plants accumulated 803.5 GDD in the first period and 808.6 GDD in the second period, from V0 to R8, with different fresh and dry mass accumulation patterns in various plant organs. This demonstrates the relationship between temperature and the growth and development of the bean plant and can provide important information for selecting the optimal planting time for this significant crop.